2015
DOI: 10.1080/15384101.2015.1010866
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a CDK4-dependent checkpoint in a conditional model of cellular senescence

Abstract: Cellular senescence, the stable cell cycle arrest elicited by various forms of stress, is an important facet of tumor suppression. Although much is known about the key players in the implementation of senescence, including the pRb and p53 axes and the cyclin dependent kinase inhibitors p16INK4a and p21CIP1, many details remain unresolved. In studying conditional senescence in human fibroblasts that express a temperature sensitive SV40 large T-antigen (T-Ag), we uncovered an unexpected role for CDK4. At the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…In this work, we pursued our experiments on CIS escape, showing that the cdk4 kinase is involved in cell emergence. As previously reported 29 , 30 , we also observed that cyclin D1 was upregulated early during CIS escape. It is not really surprising that the cdk4–E2F pathway is involved in the proliferation of PLD subclones and we can speculate that its classical cell cycle targets are involved in emergence.…”
Section: Discussionsupporting
confidence: 89%
“…In this work, we pursued our experiments on CIS escape, showing that the cdk4 kinase is involved in cell emergence. As previously reported 29 , 30 , we also observed that cyclin D1 was upregulated early during CIS escape. It is not really surprising that the cdk4–E2F pathway is involved in the proliferation of PLD subclones and we can speculate that its classical cell cycle targets are involved in emergence.…”
Section: Discussionsupporting
confidence: 89%
“…P53 can mediate cell response to DNA damage, replicative aging due to telomere shortening, as well as stress-induced premature senescence. Its downstream factor p21 can inhibit CDK2 and CDK4, rendering them unable to phosphorylate pRB [19,20]. The resultant hypo-phosphorylated pRB can bind to E2F and prevent it from binding to target genes, thereby prohibiting cells from entering the S phase.…”
Section: Influence Of Curcumin On Cellular Senescencementioning
confidence: 99%
“…complex plays a role in G1 phase, and the cell cycle enters G1 phase when CDK4 and CDK6 form active complexes with D-type cyclins. However, a recent study found that CDK4 plays an unexpected role in the G2/M checkpoint [34,35]. In this study, we…”
Section: Cinnamomi Ramulus Extracts Inhibits Cell Migration and Invasmentioning
confidence: 71%